2017
DOI: 10.7150/thno.15162
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-3p Contributes to Exercise-Induced Cardiac Growth and Protects against Myocardial Ischemia-Reperfusion Injury

Abstract: Limited microRNAs (miRNAs, miRs) have been reported to be necessary for exercise-induced cardiac growth and essential for protection against pathological cardiac remodeling. Here we determined members of the miR-17-92 cluster and their passenger miRNAs expressions in two distinct murine exercise models and found that miR-17-3p was increased in both. miR-17-3p promoted cardiomyocyte hypertrophy, proliferation, and survival. TIMP-3 was identified as a direct target gene of miR-17-3p whereas PTEN was indirectly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
240
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(246 citation statements)
references
References 28 publications
5
240
1
Order By: Relevance
“…The protective effects of exercise against cardiac I/R injury have been well acknowledged [19, 31, 38, 50], which could be associated with reduced myocardial inflammation, minimized oxidative and nitric-oxidative stress, decreased cardiomyocyte apoptosis, and promoted angiogenesis. It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of exercise against cardiac I/R injury have been well acknowledged [19, 31, 38, 50], which could be associated with reduced myocardial inflammation, minimized oxidative and nitric-oxidative stress, decreased cardiomyocyte apoptosis, and promoted angiogenesis. It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs reduce the expression of antihypertrophic factors and indirectly contribute to elevation of pathological hypertrophy. MiR-297 negatively regulates the expression of Sigma-1 receptor (Sig-1R) and activates ER stress signaling [30], while miR-17-3p targets metallopeptidase inhibitor 3 (TIMP3), a negative regulator of PTEN-Akt pathway, and resulting in cardiomyocyte hypertrophy [31]. MiR-21 targets suppressors of hypertrophic response by inhibiting translation of SH3 domain-containing protein 2 (SORBS2), PDZ, and LIM domain 5 (PDLIM5) [32].…”
Section: Mirna and Cardiac Hypertrophymentioning
confidence: 99%
“…The miR-17-92 cluster plays a critical role in cardiomyocyte proliferation (Gao et al, 2019) and affects the development of various diseases by regulating many related cellular processes and multiple target genes, including neurological diseases and cardiac diseases (Bai et al, 2019). The members of the miR-17-92 cluster and the expression of their passenger miRNAs expressions promote exercise-induced cardiac growth and reduce adverse ventricular remodeling (Shi et al, 2017). Cardiac rehabilitation will contribute in protecting against the development of depression and anxiety (Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%